2021
DOI: 10.1139/cjm-2020-0306
|View full text |Cite
|
Sign up to set email alerts
|

Crop, genotype, and field environmental conditions shape bacterial and fungal seed epiphytic microbiomes

Abstract: Seeds are reproductive structures able to carry and transfer microorganisms that play an important role in plant fitness. Genetic and external factors are reported to be partly responsible for the plant microbiome assemblage, but their contribution in seeds is poorly understood. In this study, wheat, canola, and lentil seeds were analyzed to characterize diversity, structure, and persistence of seed-associated microbial communities. Five lines and two generations of each crop were subjected to high-throughput … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 62 publications
(39 reference statements)
4
19
0
Order By: Relevance
“…It has also been shown that lettuce seeds can carry Olpidium virulentus (a Chytridiomycete) resting spores externally on the seed coat where they can eventually colonize the spermosphere and begin to infect the developing root (Maccarone, 2013)-we observed Chytridiomycete reads in cassava spermospheres. Similar to our results, some published core spermospheres have been described to contain Pantoea, Pseudomonas, Massilia, Fusarium, and/or Alternaria (Links et al, 2014;Chen et al, 2016;Klaedtke et al, 2016;Eyre et al, 2019;Chartrel et al, 2021;Moreira et al, 2021).…”
Section: Seed and Spermosphere Microbiomessupporting
confidence: 92%
“…It has also been shown that lettuce seeds can carry Olpidium virulentus (a Chytridiomycete) resting spores externally on the seed coat where they can eventually colonize the spermosphere and begin to infect the developing root (Maccarone, 2013)-we observed Chytridiomycete reads in cassava spermospheres. Similar to our results, some published core spermospheres have been described to contain Pantoea, Pseudomonas, Massilia, Fusarium, and/or Alternaria (Links et al, 2014;Chen et al, 2016;Klaedtke et al, 2016;Eyre et al, 2019;Chartrel et al, 2021;Moreira et al, 2021).…”
Section: Seed and Spermosphere Microbiomessupporting
confidence: 92%
“…However, since it has become clear that the judicious use of these microbiomes may hold the key to reproducibly promoting plant growth in the field, to study and understand seed microbiomes has become more and more important. Although the number of studies of seed microbiomes is relatively limited [ 75 , 115 , 116 , 117 , 118 , 119 , 120 ], there is a very real prospect that seed microbiomes have the ability to be transmitted to, and therefore benefit, the next generation of plants. While bacterial and fungal microbiomes may be present both on the seed surface or endophytically within the seed, it is only the endophytic organisms that can be reliably transmitted to the next generation of plants.…”
Section: Artificial Seed Microbiomementioning
confidence: 99%
“…Recent work on canola ( Brassica napus L. or B . juncea L.) bacterial communities has begun to correct this knowledge deficit (Lay et al ., 2018; Floch et al ., 2020; Taye et al ., 2020; Wang et al ., 2020; Morales Moreirda et al ., 2021). Brassicaceae oilseed‐based rotations are common throughout the world, as demand for vegetable oil and biofuels increases (Yang et al ., 2021).…”
Section: Introductionmentioning
confidence: 99%